Analisis Pemasaran Beras Semi Organik di Kecamatan Seputih Raman Kabupaten Lampung Tengah - Mubarok, Muhammad Rizqi; Lestari, Dyah Aring Hepiana; Firdasari, Firdasari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Semi organic rice is the product of rice farming that adopts environmentally friendly farming principles by replacing chemical pesticides with organic pesticides and gradually reducing the use of chemical fertilizers toward an organic farming system. However, the marketing of semi organic rice still faces challenges due to its relatively higher price and limited market segmentation. This study aims to analyze the marketing efficiency of semi organic rice in Seputih Raman District, Central Lampung Regency. The research location was determined purposively, considering the presence of the farmer group association (PP) Gapsera Sejahtera Mandiri, which has implemented a semi organic rice agribusiness system. Farmer and rice mill respondents were selected using purposive sampling, while trader respondents were selected using the snowball sampling method. Data analysis was conducted using the Structure, Conduct, and Performance (SCP) approach. The results revealed two marketing channels for semi organic rice: (I) farmer–rice mill–consumer and (II) farmer–rice mill–retailer–consumer. These channels operate within a market structure characterized by imperfect competition, including monopsony, monopoly, and oligopoly. Rice mills play a dominant role as price setters, while farmers act as price takers. The first marketing channel was found to be the most efficient, as indicated by a lower marketing margin, a farmer’s share of 42.41%, and a benefit cost ratio of 1.48.